Sobre o número Pi - Dantas, Marcelo Rodrigues Nunes (2013)
For more than 2500 years, many of the great mathematicians interested in the nature and the mysteries of fascinating number Pi , wonderful minds such that Archimedes, Euler, Gauss, Abel, Jacobi, Weierstrass, among others. In this work we will study some of the fundamental properties that characterize the number Pi. We begin our work, proving that the ratio between the length of an arbitrary circumference and its diameter is constant. For this, we use the completeness of the real numbers. This constant is precisely the number Pi. The chapter 2 is dedicated to he study of the irrationality of Pi. We present three proofs, a classical proof, due to Lambert, and two modern proofs due to Cartwright and Ivan Niven. In addition to be irrational, the number Pi is transcendental, that is, there is not a non zero polynomial in one variable with rational coeficients that has Pi as root. This fact was initially proved by Lindemann and as a consequence, the classical problem of squaring the circle has no solution. In the chapter 3 we present , without proof, a more general result, the celebrated Lindemann-Weierstrass theorem, which has a corollary , the transcendence of Pi. Finally, in the chapter 4, chronology, curiosities, approximations and series on Pi are studied.